Integrated single-cell RNA-seq analysis identifies immune heterogeneity associated with KRAS/TP53 mutation status and tumor-sideness in colorectal cancers - Liu, Xiaoyu; Xu, Xu; Wu, Zhuozhuo; Shan, Qungang; Wang, Ziyin; Wu, Zhiyuan; Ding, Xiaoyi; Huang, Wei; Wang, Zhongmin (Frontiers in Immunology, 2022)
Background The main objective of this study was to analyze the effects of KRAS/TP53 mutation status and tumor sideness on the immune microenvironment of colorectal cancer using integrated scRNA-seq data. Methods A total of 78 scRNA-seq datasets, comprising 42 treatment-naive colorectal tumors, 13 tumor adjacent tissues and 23 normal mucosa tissues were included. Standardized Seurat procedures were applied to identify cellular components with canonical cell marks. The batch-effect was assessed and corrected using harmony algorithm. The scMetabolism algorithm was used for single-cell metabolic analysis. The results and clinical significance were further validated using immunofluorescent-staining and TCGA-COAD datasets. Immune-infiltration scores of bulk-RNA-seq data were estimated using ssGSEA. The presto-wilcoxauc algorithm was used to identify differentially enriched genes or pathways across different subgroups. Two-sided p-value less than 0.05 was considered statistically significant. Results We refined the landscape of functional immune cell subtypes, especially T cells and myeloid cells, across normal mucosa, tumor adjacent and tumor tissue. The existence and function of two states of exhausted CD8+ T (Tex) subtypes in colorectal cancer, and FOLR2+ LYVE1+ macrophages indicating unfavorable prognosis in colorectal cancer were identified and validated. The diverse tumor mutation status reshaped the immune cell function and immune checkpoint ligands/receptors (ICLs/ICRs) expression pattern. Importantly, the KRAS/TP53 dual mutations significantly reduced the major energy metabolic functions in immune cells, and promoted the cell-to-cell communications towards immunosuppression in colorectal cancers. The results revealed LAG3, CD24-SIGLEC10 and HBEGF-CD9 pathways as potential therapeutic targets for dual mutant colorectal cancers. Conclusions We revealed that the immune microenvironment underwent a gradual remodeling with an enrichment of immunosuppressive myeloid cells from normal mucosa to tumor regions in colorectal cancers. Moreover, we revealed the metabolic heterogeneity of tumor-infiltrating immune cells and suggested that the KRAS/TP53 dual mutation may impair antitumor immunity by reducing T and myeloid cell energy metabolism and reshaping cellular interactions toward immunosuppression.